Evaluation of various density functionals for predicting the electrophosphorescent host HOMO, LUMO and triplet energies - Ong, B.K.; Woon, Kai Lin; Ariffin, Azhar (Elsevier, 2014)
Design of phosphorescent hosts for deep blue emitter with suitable electronic states for high efficiency electrophosphorescent light emitting diodes is often carried out by using wet-lab techniques and trial and error. Although, quantum computation has been carried out to study the influence of certain substituents on the materials, an accurate prediction of the highest occupied molecular orbital (HOMO), the lowest unoccupied molecular orbital (LUMO) and the triplet energies (ET) of electrophosphorescent hosts remains challenging. Here, we evaluate different density functionals on a set of electrophosphorescent hosts of different sizes using time-dependent density functional theory. M062X is found to be the best predictor for ET. Other methods such as B3LYP and O3LYP are potentially good estimators for HOMO and LUMO levels. By using empirical relationships between the predicted HOMO, LUMO and ET energies with respect to the experimental values, more accurate estimations can be obtained. The empirical relationships mean absolute error for ET, LUMO and HOMO energy levels are 0.11 eV, 0.21 eV and 0.17 eV, respectively. These techniques are used to predict a new electron transporting electrophosphorescent host. These empirical relationships would greatly assist in the accurate prediction of electronic states of solution processable electrophophorescent hosts.